Knowledge About Sexual Relationship And Frequency Of Sexual Contact In Pregnant Women In Third Trimester At Pmb Noferia Raraswati Mojosari-Mojokerto - Anggrawati Wulandari; Lingga Kusuma Wardani; Indah Triningsih; Ida Nuryanti (Journal of Health Science Community, 2023)
The reduced frequency of sexual intercourse among third trimester pregnant women is due to a lack of knowledge about sexual intercourse during pregnancy and pregnant women are afraid of hurting their fetus. The aim of this research is to analyze the relationship between knowledge about sexual intercourse and the frequency of sexual intercourse among third trimester pregnant women at PMB Noferia Raraswati Mojosari.This research uses design observational analytics with cross sectional approach. The variables in this research consist of 2 variables, as many as the dependent variable and the independent variable using an ordinal scale. The population in this study were all third trimester pregnant women who visited PMB Noferia Raraswati Mojosari-Mojokerto in April-May 2020 with a sample of 32 third trimester pregnant women. The sampling technique used is simple random sampling and data collection techniques in this research used the questionnaire method. Statistical tests in this study used Spearman correlation with a significant level of α = 0.05. The ethics considered in this research consist of: informed consent (Respondent consent sheet), anonymity (Without a name), confidentiality (Confidentiality). The results of the study showed that there was a relationship between knowledge about sexual intercourse and the frequency of sexual intercourse among pregnant women in the third trimester at PMB Noferia Raraswati Mojosari-Mojokerto with the value P value < α = 0,05 (0,006 < 0,05).Knowledge about sexual intercourse influences the frequency of sexual intercourse among third trimester pregnant women at PMB Noferia Raraswati Mojosari-Mojokerto.